Histological mapping of healing of the small and large intestine - A quantitative study in a porcine model - Kural, Tomáš; Grajciarová, Martina; Rosendorf, Jáchym; Pálek, Richard; Červenková, Lenka; Malečková, Anna; Šarčevic, Sima; Liška, Václav; Tonar, Zbyněk (Annals of anatomy, 2023)
BACKGROUND: Gastrointestinal anastomoses are performed in many patients every year. The pathogenesis of aberrant anastomotic healing and the causes of intestinal leakage are not fully understood. The present study gathered and critically evaluated histological quantitative data to deepen current knowledge of anastomotic healing in the small and large intestine and its complications and outline the options for further experimental in vivo research in large porcine animal models. METHODS: Three groups of porcine intestinal anastomoses were compared: small intestine without defect (SI; n = 7), small intestine with an additional defect (SID; n = 8), and large intestine (LI; n = 7). Multilevel sampling (2112 micrographs) and stereological methods were used for histological quantification of proliferation (Ki-67 immunohistochemistry), neutrophil infiltration (myeloperoxidase staining), vascularity (von Willebrand factor) and type I and type III collagen formation (picrosirius red in polarized light) within the region of anastomosis compared to the region outside of anastomosis. RESULTS: Quantitative histological evaluation revealed the following results. i) Proliferation, vascularity, and collagen, but not neutrophils, were more highly expressed within the anastomosis than outside of the anastomosis region. ii) Porcine large and small intestine were not interchangeable based on histological evaluation of surgical experiments. The presence or absence of an additional experimental defect strongly affected healing, but the healing seemed complete after 21 days. iii) The microscopic structure of small intestine segments was more affected by their proximity to the anastomosis than the structure of large intestine segments. CONCLUSIONS: Histological quantification was more laborious than the previously used semiquantitative scoring system evaluating the healing rate of intestinal anastomoses, but it provided detailed maps of biological processes within individual intestine layers. The primary data collected in the study are open and available for power sample analyses to calculate the minimum numbers of samples justified in future experiments on porcine intestines. The porcine intestine is a promising animal model with translational potential for human surgery.
Keywords: prasata; Experimental surgery; Swine; střeva; Intestine, Large; Large intestine; Intestine, Small; tlusté střevo; anastomóza chirurgická; Anastomosis; Small intestine; Stereology; Animals; lidé; Wound Healing; Pig; Humans; zvířata; Anastomosis, Surgical; tenké střevo; Intestines; Histology; hojení ran